Pengaruh Likuiditas, Aktivitas Dan Solvabilitas Perusahaan Terhadap Profitabilitas Pada Industri Farmasi Yang Listing Di Bursa Efek Indonesia 2013-2017 - M Irfan Syaifani (Science of Management and Students Research Journal (SMS), 2019)
Research Objectives To Know the Effect of Company Liquidity, Activities and Solvability on Profitability in the Pharmaceutical Industry in Indonesia Stock Exchange Period 2013-2017 simultaneously and partially. The object of this analysis is the subsector of the pharmaceutical consumer goods manufacturing industry listed on the Indonesia Stock Exchange for the period 2013-2017. The sample used in this study is 7 industries including the pharmaceutical industry listed on the Indonesia Stock Exchange in the period 2013-2017. The method used is a quantitative method with independent variables, Current Ratio, Total Equity, and Debt to Equity Ratio while the dependent variable is Return on Asset. The analytical tool used in this study is multiple linear regression analysis, classical assumption test (normality, multicollinearity, hetoroscedasicity, and autocorrelation), coefficient of determination and correlation coefficient.Based on the results of multiple linear regression analysis shows the equation Y = 1.138 + 0.323X1 + 0.144X2 - 0.411X3 + e with the F test value of 3.963. T test value for Debt Ratio to Current Ratio 1,204, Total Equity 1,030 and Debt to Equity Ratio -1,704. t test value of the Company Size of 2,048. The value of R Square is 29.8%, while the remaining 71.2% explains other factors outside the research model.The conclusion of this study shows that the Debt Ratio to Current Ratio, Total Equity and Debt to Equity Ratios simultaneously have a significant effect on Return on Assets. Partially Current Ratio does not have a significant effect on Return on Assets, Total Equity does not have a significant effect on Return on Assets while the Debt to Equity Ratio variable does not have a significant effect on Return on Assets. Suggestions for further research are expected to consider the sample of companies that will be used because it will affect the results to use the latest studies and longer intervals in the study to provide further details about the factors that influence company profits.